12.42% Monolithic 25.42 cm2 Flexible Organic Solar Cells Enabled by an Amorphous ITO‐Modified Metal Grid Electrode. Issue 17 (25th March 2022) - Han, Yunfei; Hu, Zishou; Zha, Wusong; Chen, Xiaolian; Yin, Li; Guo, Jingbo; Li, Zhiyun; Luo, Qun; Su, Wenming; Ma, Chang‐Qi
Abstract: Printed metal nanogrid electrode exhibits superior characteristics for use in flexible organic solar cells (OSCs). However, the high surface roughness and inhomogeneity between grid and blank region is adverse for performance improvement. In this work, a thin amorphous indium tin oxide (ITO) film (α‐ITO) is introduced to fill the blank and to improve the charge transporting. The introduction of α‐ITO significantly improves the comprehensive properties of metal grid electrode, which exhibits excellent bending resistance and long‐term stability under double 85 condition (under 85 °C and 85% relative humidity) for 200 h. Both experimental and simulation results reveal α‐ITO with a sheet resistance of 20 000 Ω □ −1 is sufficient to improve the charge transporting within the adjacent grids, leading to a remarkable efficiency of 16.54% for 1 cm 2 flexible devices. With area increased to 4.00, 9.00, and 25.42 cm 2, the devices still display a performance of 16.22%, 14.69%, and 12.42%, respectively, showing less efficiency loss during upscaling. And the 25.42 cm 2 monolithic flexible device exhibits a certificated efficiency of 12.03%. Moreover, the device shows significantly improved air stability relative to conventional high‐conductive poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate‐modified device. All these make the α‐ITO‐modified Ag/Cu electrode promise to achieve high‐efficient and long‐term stable large‐area flexible OSCs. Abstract : 12.42% monolithic 25.42 cm 2 flexible organic solar cells (OSCs) are reported based on the nanogrid electrodes modified by amorphous indium tin oxide (ITO) modification layer. The modification of amorphous ITO also ensures excellent air shelf stability, as well as mechanical properties.